Potencialidades da pimenta biquinho (Capsicum chinense) como aditivo natural - Silva, Everton Vieira da (2017)
The Capsicum ssp, popularly known as pepper, is among the most consumed products in the world, especially those that present higher pungency. Some are used only for ornamental dishes or as seasonings and simple condiments like pout pepper, it not having their properties physical, chemical and biological valued. This study aimed to evaluate the potential of pout pepper (Capsicum chinense) as natural additive in food formulations. Obtained bran and the liquid dye were applied to the production of cookies in replacing artificial dye and ammoniac, is being evaluated during 90 days of storage. The extract was also elaborated, applied in the production of yogurt to replace the dye and potassium sorbate and evaluated for 40 days. All products were characterized through physical and chemical tests. The antioxidant potential of bran, dye and extract were checked by the methods of DPPH, ABTS and phenolic compounds, in addition, the major compounds of the additives ware determined by HPLC. The cookies and yogurts produced were also sensorially evaluated by 100 untrained tasters. The elaborated additives have accented levels of phenolic compounds, food pigments and a considerable antioxidant activity, they also present capsaicin, dihydrocapsaicin, quercetin, apigenin, myricitrin as marjorite compounds. In the dye, it was checked low percentage of minerals, high bran protein and mineral content and low percentage of lipids. The cookies produced with total replacement of ammoniac and artificial dye were stable throughout the 90 days and they were accepted sensorially. The yogurts with higher concentration of extract (0.3%) showed more stable during storage of 40 days and have also had good acceptance by the tasters. In addition, all items produced have satisfactory hygienic and sanitary conditions. This research concludes that the pout pepper has several potential as natural additive, it can be applied in the food industry, contributing to a more natural production and without risk to the consumer health.